EFEKTIVITAS KINERJA KEUANGAN BERDASARKAN DU PONT SYSTEM DAN TIME SERIES APPROACH PADA PT. SUCOFINDO PERIODE 2018 – 2022 - Dinesta, As-sakhra Nurazizah; Sudrartono, Tiris (Economic Education, University of Jember, 2024)
This study aims to assess the effectiveness of financial performance at PT Sucofindo and identify factors that affect the rise and fall of the profitability level of a company. Using the Du Pont System approach and Time Series Approach analysis. The variables analyzed are Net Profit Margin, Total Asset Turnover, Multiplayer Equity Ratio, Return On Investment, and Return On Equity. This research uses a descriptive method with a quantitative approach. The data used is secondary data, which refers to information obtained from pre-existing sources such as in this study taken from the PT. Sucofindo website for the period 2018 - 2022. The results of the study can be concluded that NPM with an average of 10.48% is in the effective criteria. Average TATO worth 0.71 times occupies ineffective criteria. MER with an average value of 1.35 times is in the effective criteria. ROI of 7.44% is in the ineffective criteria. And ROE with an average of 9.98% is in fairly effective criterion. The suggestions from the results of this study are to increase the volume of service revenue and expand market share to maintain the company's financial stability and to streamline the use of capital and assets to achieve the goals of the company.